Síndrome de Budd-Chiari e Trombocitopenia grave em doente com Lúpus Eritematoso Sistémico e Síndrome Antifosfolípido Secundária - Duarte, C (2007)
Systemic Lupus Erythematosus (SLE) is a rheumatic autoimmune disease characterized by multisystemic involvement with a variable prognosis. The association with Antiphospholipid Syndrome (APS) occurs in about 36% of the patients, raising additional problems with treatment and monitoring of these patients. The authors report a clinical case of a girl with SLE and APS who represented Budd-Chiari Syndrome and severe thrombocytopenia. The patient had severe thrombotic event and simultaneously a high hemorrhagic risk due to thrombocytopenia. Long-term resolution of the thrombocytopenia was achieved with mycophenolate mofetil. Long-term anticoagulation for thrombosis prophylaxis is required